E-Learning adoption during COVID-19 crisis and its effect on achieving students' performance: Evidence from Jordanian universities - Nazem Malkawi; Mohammad haider S. Mohailan (OmniaScience, 2022)
This study aimed to know the effect of E-Learning with all its components on students' performance at Jordanian Universities during at COVID-19 crisis.      To achieve study goals, a questionnaire was distributed to the students at Jordanian Universities, (870) valid questionnaires were recovered. The study found that: The level of E- Learning and its components at Jordanian Universities were at middle rates, students' performance also comes at a moderate level. E- Learning and its components (Technological facilities readiness, Electronic applications readiness, Databases & E-resources readiness, People readiness, E-learning management system readiness, Evaluation system readiness, teaching methods diversity, Educational curricula and electronic content readiness) have a significant effect on students' performance at Jordanian Universities at significance (α ≤ 0.05). Whereas subcomponents of (E-learning organizational environment readiness and legislations and regulations readiness) have no effect separately on students' performance. The study recommended Jordanian Universities to improve E- Learning in all its components in the Universities, reinforce using E- Learning in education, and exploit the benefits of E- Learning to improve students' performance because it is the main alternative to face emerging crises like Coronavirus.